Purification and characterization of Clostridium difficile toxin. - Rolfe, R D (1979)
Recent evidence indicates that toxigenic Clostridium difficile strains are a major cause of antimicrobial-associated ileocecitis in laboratory animals and pseudomembranous colitis in humans. C. difficile ATCC 9689 was cultivated in a synthetic medium to which 3% ultrafiltrated proteose peptone was added. Purification of the toxin from broth filtrate was accomplished through ultrafiltration (100,000 nominal-molecular-weight-limit membrane), precipitation with 75% (NH4)2SO4, and chromatographic separation using Bio-Gel A 5m followed by ion-exchange chromatography on a diethylaminoethyl-Sephadex A-25 column. The purified toxin displayed only one band on polyacrylamide gel electrophoresis, and approximately 170 pg was cytopathic for human amnion cells. The isolated toxin was neutralized by Clostridium sordelli antitoxin, heat labile (56 degrees C for 30 min), and inactivated at pH 4 and 9; it had an isoelectric point of 5.0, increased vascular permeability in rabbits, and caused ileocecitis in hamsters when injected intracecally. Treatment of the toxin with trypsin, chymotrypsin, pronase, amylase, or ethylmercurithiosalicylate caused inactivation, whereas lipase had no effect. By gel filtration, its molecular weight was estimated as 530,000. Upon reduction and denaturation, the toxin dissociated into 185,000- and 50,000-molecular-weight components, as determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Extensive dissociation yielded only the 50,000-molecular-weight component. The toxin appears to be protoplasmic and is released into the surrounding environment upon autolysis of the cells. Attempts to correlate specific enzymatic activity with the toxin have been unsuccessful. These studies will help delineate the role of C. difficile toxin in antimicrobial-associated colitis and diarrhea.